Therapeutic Options for Chronic Rhinosinusitis in N-ERD Patients - van der Lans, Rik J. L.; Fokkens, Wytske J.; Reitsma, Sietze (Frontiers in Allergy, 2021)
Patients with non-steroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (N-ERD) often suffer from chronic rhinosinusitis (CRS) with nasal polyps, a form of primary diffuse Type 2 CRS. Although this disease is also seen in NSAID-tolerant patients, CRS in N-ERD often is more severe and more treatment resistant; local nasal therapy (nasal corticosteroids) and endoscopic sinus surgery are employed like in NSAID-tolerant patients, but with limited and/or short-lived effects. This mini-review gives an overview of the current additional treatment options for CRS in N-ERD. As such, diets, aspirin therapy after desensitization, antileukotriene therapy and biologicals are discussed based on the current body of literature. Selecting the right treatment strategy depends on shared-decision making, local availability and cooperation between ENT-surgeons, allergists, and pulmonologists.